Illocutive characteristics of deontic I- and We-constructions (based on the material of the Russian and German) - Sytko, Anna W. (Journal of the Belarusian State University. Philology, 2021)
The paper analyses the illocutionary characteristics of deontic I- and We-constructions. The analysis is carried out based on two languages, German and Russian. It is noted that deontic I- and We-constructions are the most frequent in the corpora of two languages. It is shown that different semantic types of propositional verbs functioning in these modal constructions have different frequency in the corpora of two languages. It is noted that differences in the system of deontic markers do not have a significant impact on the pragmasemantics of modal utterance in two languages, but they make it possible in Russian to nuance its illocutionary characteristics. Based on the methodological criterion of compliance of the felicity conditions the communicative orientation of the modal utterance is revealed. The functional variability of these constructions is described. The factors are determined that determine the formation of pragmatic semantics of constructions with the modal subject of two types (I – We). It is proved that the directive semantics traditionally attributed to deontic constructions is realised only in the case of an inclusive We-subject. It is shown that the functional semantics of the I- and We-constructions depends on the semantic type of the propositional verb. It is revealed that certain illocutions (commissive, interrogative) has specific realisation nature. It is shown that the proposed pragmatic approach makes it possible to reveal the pragmasemantic diversity of modal utterance.